Batman/Superman, world's finest. Vol. 3, Elementary - Waid, Mark, 1962- (DC Comics, 2024)
"In the pages of World's Finest, Batman, Robin, and Superman have traversed some of the DCU's most iconic locations and teamed up with the likes of the Teen Titans, Doom Patrol, and Supergirl, but none of that will prepare them as they must go across the globe in search of Rex Mason, a.k.a. Metamorpho, the Element Man! The World's Finest Strangest Adventure begins here!"--Amazon.